Tropical origin of the severe European winter of 1962/1963. (26th March 2014) - Greatbatch, R. J.; Gollan, G.; Jung, T.; Kunz, T.
<x xml:space="preserve">Abstract</x> A set of relaxation experiments using the European Centre for Medium‐Range Weather Forecasts (ECMWF) atmospheric model is used to analyze the severe European winter of 1962/1963. We argue that the severe winter weather was associated with a wave train that originated in the tropical Pacific sector (where weak La Niña conditions were present) and was redirected towards Europe, a process we suggest was influenced by the combined effect of the strong easterly phase of the Quasi‐Biennial Oscillation (QBO) and unusually strong easterly winds in the upper equatorial troposphere that winter. A weak tendency towards negative North Atlantic Oscillation (NAO) conditions in December, associated with extratropical sea‐surface temperature and sea‐ice anomalies, might have acted as a favourable preconditioning. The redirection of the wave train towards Europe culminated in the stratospheric sudden warming at the end of January 1963. We argue that in February the sudden warming event helped maintain the negative NAO regime, allowing the severe weather to persist for a further month. A possible influence from the Madden–Julian Oscillation, as well as a role for internal atmospheric variability, is noted.